Gendered Paths to Asset Accumulation? Markets, Savings, and Credit in Developing Countries - Doss, C.R.; Deere, C.D.; Oduro, A.D.; Swaminathan, H.; Catanzarite, Z.; Suchitra, J.Y. (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
Keywords: Asset markets; Inheritance; Ecuador; Ghana; India